EDUKASI PENCEGAHAN PENYEBARAN COVID-19 SECARA ONLINE PADA MASYARAKAT KOTA BAUBAU - Sabarudin Sabarudin; Rifa’atul Mahmuddah; Ruslin Ruslin; La Aba; Nanik Hindaryatiningsih; La Ode Nggawu; Syahbudin Syahbudin; Fifi Nirmala G.; Sari Sukmawati Kapota; Hasyim Abdillah (Jurnal Pengabdian NUSANTARA, 2021)
This community service aims to help the Baubau City Government improve public knowledge in preventing and fighting the Covid-19 virus. This service is done in the form of online education through social media platforms namely Facebook, WhatsApp, and Instagram. Besides, to support online socialization as a tangible form of concern for the people of the city of Baubau, the distribution of masks and hand sanitizers was carried out. The method used in this community service activity is through education using leaflets and video media about the prevention of COVID-19 transmission and the distribution of masks and hand sanitizers. Community service activities in the city of Baubau have been completed and have been socialized in the city of Baubau by conducting online socialization using leaflets and videos and providing education related to Covid-19 with the socialization activities of the Healthy Living Movement (Germas), socialization activities of the Community Movement Using Masks (Masks) Anxious), Clean and Healthy Life Behavior (PHBS) socialization activities, immunomodulatory socialization activities, socialization activities on the use of antiseptics and disinfectants, as well as activities on the distribution of fabric masks and hand sanitizers.